1998
DOI: 10.1111/j.1744-7348.1998.tb05226.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of salt on rhizobia and bradyrhizobia: a review

Abstract: Rhizobia and bradyrhizobia strains vary in their tolerance to salt-stress. Rhizobium strains (fast-growers) are more salt-tolerant than strains of Brudyrhizobiuin (slow-growers). However, salt-tolerance in both genera is dependent upon ionic species, pH value, temperature, carbon source and the presence of osmoprotectant solutes. The harmful effect of salts on growth of both genera can be attributed to the specific ion effect rather than the osmotic effect. The salttolerance of different strains of rhizobia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
2
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 89 publications
(137 reference statements)
2
15
2
2
Order By: Relevance
“…This result contrasts with the frequent conclusion that rhizobial growth rate and salt‐tolerance are positively correlated (e.g. Elsheikh 1998; Marsudi et al . 1999; Barboza et al .…”
Section: Discussioncontrasting
confidence: 87%
“…This result contrasts with the frequent conclusion that rhizobial growth rate and salt‐tolerance are positively correlated (e.g. Elsheikh 1998; Marsudi et al . 1999; Barboza et al .…”
Section: Discussioncontrasting
confidence: 87%
“…Higher concentrations inhibited growth. The results for this strain are thus similar to those presented by Boncompagni et al (1999) for B. japonicum USDA 110 and the strains surveyed by Elsheikh (1998).…”
Section: Growth In Liquid Medium With Different Concentrations Of Naclsupporting
confidence: 90%
“…Several strains of B. japonicum were reported as salt-sensitive compared to other rhizobia (Elsheikh 1998). The usual procedure to determine sensitivity is to grow the strain in media of increasing salinity and determine the cell count obtained at each salt concentration, NaCl is the most frequently tested salt.…”
Section: Growth In Liquid Medium With Different Concentrations Of Naclmentioning
confidence: 99%
“…In a previous study, Fall et al (2008) showed that the three strains tolerated 20% of PEG 6000 and 1.5% of NaCl but a combination of high concentration of PEG 6000 (20%) and NaCl (1.5%) depressed strain growth. These two compounds have osmotic effects on rhizobial cells (El Sheikh EAE 1998;Räsänen et al 2004). One response of rhizobia to osmotic stress is morphological change which leads to a reduction in growth (Shoushtari and Pepper 1985;Busse and Bottomley 1989).…”
Section: Discussionmentioning
confidence: 97%